Outline of money - Crowther, Geoffrey (London, 1963)
What is Money? That is a question which few people Wcan answer, although nearly everybody thinks he knows the answer. It is reminiscent of the man who was asked to define an elephant and could only reply that he would know one when he saw one. Everybody knows in practice what constitutes money, but few people would be prepared at a moment's notice to define money, to indicate precisely what differentiates money from other articles or commodities. This book is concerned with money, and it is an obvious preliminary to make it quite clear what we are talking about. But it will take a whole chapter to define money, and even then the definition can only be made intelligible to the layman by means of description. The dictionary defines an elephant as a mammal of Africa and India, having the snout prolonged into a prehensile proboscis'; but this would hardly be of much assistance in identifying the animal. Similarly, the dictionary definition of money as anything having a customary or conventional use as a medium of exchange or a measure, or denominator, of value' is comprehensive, but hardly precise or illuminating.
Keywords: Economics